2010
DOI: 10.1159/000320190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model to Predict Outcomes in Non-Small Cell Lung Cancer Patients with Erlotinib as Salvage Treatment

Abstract: Purpose: To devise a prognostic model based on clinical parameters for non-small cell lung cancer (NSCLC) patients treated with erlotinib as a salvage therapy. Patients and Methods: Between July 2006 and September 2008, two hundred fifty-seven metastatic/relapsed NSCLC patients who had been treated with erlotinib as a salvage therapy were analyzed retrospectively. Results: For the 257 patients, the median overall survival (OS) and progression-free survival (PFS) with erlotinib treatment were 12.4 and 2.8 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…However, in our study, smoking history was not significantly associated with OS. This finding is similar to the results of two recent Asian studies (Uhm et al, 2009;Kim et al, 2010). These studies reported that, on a multivariate level, smoking status did not retain significance for OS or time to progression in patients with advanced NSCLC who were treated with erlotinib as a salvage therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in our study, smoking history was not significantly associated with OS. This finding is similar to the results of two recent Asian studies (Uhm et al, 2009;Kim et al, 2010). These studies reported that, on a multivariate level, smoking status did not retain significance for OS or time to progression in patients with advanced NSCLC who were treated with erlotinib as a salvage therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Of these prognostic factors, PS, weight loss, and the number of prior regimens played a significant prognostic role for OS in our study. In two recent retrospective studies, an ECOG PS of 2 or more, elevated serum LDH, and the absence of skin rash (Kim et al, 2010), as well as low BMI, stage IV disease, anaemia at diagnosis, and male gender (Hsu et al, 2012), were shown to be adverse prognostic factors for OS. Unlike these previous studies, the presence of an intra-abdominal metastasis was a negative prognostic factor for survival in patients with metastatic NSCLC treated with erlotinib in our study.…”
Section: Discussionmentioning
confidence: 99%
“…And a previously reported study also demonstrated that the presence of intra-abdominal metastasis was correlated with poor prognosis in NSCLC patients treated with erlotinib as salvage therapy. 14 In univariate analysis, patients treated with EGFR TKI as first-line treatment seemed to have a longer PFS than those with prior cytotoxic chemotherapy before EGFR TKI treatment. However, longer PFS trend associated with first-line EGFR TKI treatment was diminished in then multivariate analysis (hazard ratio, 1.32; 95% CI 0.92-1.88; p = 0.135).…”
Section: Efficacy and Clinical Outcomes Of Egfr Tkismentioning
confidence: 97%
“…Such differences are important, as at least age, performance status, and tumour stage were predictors of progression-free survival (PFS) in NSCLC. 7,[17][18][19] …”
Section: Study Characteristics Study Measurements and Patient Charamentioning
confidence: 99%